2000
DOI: 10.2172/758753
|View full text |Cite
|
Sign up to set email alerts
|

Control of alkali species in gasification systems: Final report

Abstract: Gas-phase alkali metal compounds contribute to fouling, slagging, corrosion, and agglomeration problems in energy conversion facilities. One mitigation strategy applicable at high temperature is to pass the gas stream through a fixed bed of sorbent or getter material, which preferentially adsorbs alkali via physical adsorption or chemisorption. This report presents results of an experimental investigation of high-temperature (600° to 700°C) alkali removal from a hot filtered gasifier product gas stream using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 20 publications
0
22
1
Order By: Relevance
“…That is why silicon-, calcium-, and iron-rich coarse PM could have been impacted on lower stages, as found elsewhere [7,28]. However, it was also reported that these elements could volatilize to a certain extent even at temperatures as low as 800°C [38].…”
Section: Fine Modementioning
confidence: 61%
“…That is why silicon-, calcium-, and iron-rich coarse PM could have been impacted on lower stages, as found elsewhere [7,28]. However, it was also reported that these elements could volatilize to a certain extent even at temperatures as low as 800°C [38].…”
Section: Fine Modementioning
confidence: 61%
“…The main reactions taking place in CO 2 sorbent enhanced gasification can be written as Eqs. (1)-(3), provided that a typical woody biomass CH 1.5 O 0.7 [3] is used. The abundant CaO loaded to the gasifier plays two important roles: (1) absorbing the released CO 2 to enhance the water gas (Eq.…”
Section: Introductionmentioning
confidence: 99%
“…This would reduce the risks for weakening by high temperature corrosion. Alkalis could be removed in fixed beds with sorbents, such as, bentonites or bauxites [48,49]. Sulphur and chlorine by adding sorbents, such as CaO [47], to be removed as CaS and CaCl 2 either in a fixed bed or a cyclone, upstream the particulate candle filter.…”
Section: Opportunities: Selected Examplesmentioning
confidence: 99%